Evidence based social media use: an exploratory UK investigation into residents' perceptions of police Facebook use. Issue 2 (28th May 2020) - Cartwright, Ashley; Shaw, Chloe
Abstract : Purpose: Social media is an integral part of modern society and is used by billions of people worldwide. In a policing context, police services are starting to use social media platforms to interact with their communities. However, academic literature is lagging regarding the effectiveness of police use of social media. The purpose of this study is to gather public perceptions regarding the police's use of social media particularly the use of Facebook. Design/methodology/approach: The study administered a cross sectional survey recruiting participants who are policed by one of the larger police services in England and Wales. A total of 294 respondents completed the survey providing their views on their police service's use of social media. Findings: The results of the present study provide overwhelming support for the police's use of social media by the public, with most respondents actively following their local police service's social media accounts. The study additionally provides a number of important findings in relation to the preferences of the public with regards to their police service's use of Facebook. Practical implications: The findings presented here provide police services with an insight into how to implement an evidenced-based approach to their social media activity. Originality/value: The present study takes an alternative approach to understanding the effectiveness of police social media use by simply asking residents, an approach not used in this area of policing research to date.